Positive definite measures with discrete Fourier transform and pure point diffraction - Strungaru, Nicolae (My University, 2011)
In this paper we characterize the positive definite measures with discrete Fourier transform. As an application we provide a characterization of pure point diffraction in locally compact Abelian groups.
Keywords: pure point diffraction; positive definite measure; Fourier transform of measures